Fahr’s syndrome with hypoparathyroidism in a 65 year old: a case report - Sirohi, Parmendra; Vishwakarma, Manaswi; Gupta, Rahul; Sharma, Peeyush; Verma, Abhishek (International Journal of Research in Medical Sciences, 2024)
Fahr’s syndrome also known as idiopathic basal ganglia calcification (IBGC) is a notably rare neurological disease with an autosomal dominant pattern of inheritance and genetic heterogeneity, resulting from symmetric bilateral calcification commonly in basal nuclei and cerebellum. Regardless of being a rare disorder, Fahr’s can have a dramatic effect on patients, and is characterized by spectrum of metabolic, biochemical, neuro-radiological, and neuro-psychiatric alterations leading to cognitive dysfunction, motor impairment and neurological manifestations. Our case of a 65-year male, deals with array of varied clinical symptoms and diagnostic difficulties of Fahr’s associated with hypoparathyroidism. The case report contributes to the expanding comprehension of the Fahr’s highlighting its genetic aspect and clinical heterogeneity and developing avenues for appropriate diagnostic and imaging modalities as-well-as intervention techniques. The motives of this article extend beyond the clinical case, influencing future research, diagnostic and prevention strategies.